2021
DOI: 10.1158/1078-0432.ccr-21-3435
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab Plus Endocrine Therapy or Chemotherapy as First-line Treatment for Patients with Hormone Receptor–Positive and HER2-Positive Metastatic Breast Cancer (SYSUCC-002)

Abstract: Purpose: There is no research evidence demonstrate which is the better partner strategy, endocrine therapy or chemotherapy, to combine with anti-HER2 therapy as the first-line management of hormone receptor (HR)-positive (HR+) and HER2-positive (HER2+) metastatic breast cancer (MBC). We wished to ascertain if trastuzumab plus endocrine therapy is noninferior to trastuzumab plus chemotherapy. Patients and Methods: We conducted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 41 publications
(58 reference statements)
0
26
0
Order By: Relevance
“…However, these results were not adjusted for the type of ERBB2 -targeted therapy or treatment combination . In 2022, a phase III noninferiority trial reached its objective comparing ET with trastuzumab vs CT with trastuzumab. The study did not include the current first-line standard of care with dual- ERBB2 blockade, but it further supported the frequent use of ET observed in the clinical practice given that it also found a significantly higher prevalence of toxic effects in the CT group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these results were not adjusted for the type of ERBB2 -targeted therapy or treatment combination . In 2022, a phase III noninferiority trial reached its objective comparing ET with trastuzumab vs CT with trastuzumab. The study did not include the current first-line standard of care with dual- ERBB2 blockade, but it further supported the frequent use of ET observed in the clinical practice given that it also found a significantly higher prevalence of toxic effects in the CT group.…”
Section: Discussionmentioning
confidence: 99%
“…Current European guidelines recommend dual ERBB2 blockade with trastuzumab and pertuzumab (T+P) and CT for ERBB2+ MBC first-line therapy, regardless of HR status, and ET only during maintenance or if the patient is unfit for CT. 4 National Comprehensive Cancer Network (NCCN) guidelines mention ET alone or in combination with ERBB2-targeted therapy as an approach with lower levels of toxic effects for first-line therapy in these patients. 5 Moreover, a 2022 phase III randomized clinical trial 6 found that trastuzumab with ET was noninferior to trastuzumab with CT in patients with HR+/ERBB2+ MBC. Therefore, the role of ET in this setting is not well established, particularly in the context of the current standard first-line therapy that includes dual-ERBB2 blockade.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommended first‐line therapy is currently dual HER2 blockade with trastuzumab and pertuzumab in combination with chemotherapy (preferably taxanes) [ 204 , 205 ]. Patients with HR‐positive and HER2‐positive tumors have the alternative of receiving ET in combination with HER2‐targeted therapy [ 206 , 207 , 208 ]. The second line options include trastuzumab deruxtecan (T‐DXd), T‐DM1, and pyrotinib (approved in China).…”
Section: Mbcmentioning
confidence: 99%
“…The HER2+ breast cancer subtype is defined by assessment of HER2 expression by immunohistochemistry (score 3+ or 2+ with positive ISH), and the standard of care treatment is trastuzumab, a monoclonal antibody directed to the HER2 molecule [ 12 ], which is administered based on the results of HER2 expression. In the case of HER2+ breast cancer with positive hormone receptors (luminal B), endocrine therapy is incorporated into the trastuzumab and chemotherapy administration [ 13 , 14 ]. There are several prognostic biomarkers for HER2+ breast cancer, but no predictive biomarkers to determine which HER2-targeted therapy will be more effective for the patient.…”
Section: Introductionmentioning
confidence: 99%